Platelet-rich fibrin-mediated revitalization of immature necrotic tooth - Navin Mishra; Isha Narang; Neelam Mittal (Wolters Kluwer Medknow Publications, 2013)
Contemporary studies have shown that the regeneration of tissues and root elongation is possible in necrotic immature permanent teeth. The purpose of this case report is to add a new vista in regenerative endodontic therapy by using platelet rich fibrin for revitalization of immature non vital tooth. An 11year old boy with the history of trauma was diagnosed with the pulpal necrosis and symptomatic apical periodontitis in tooth #21. Intra oral periapical radiograph showed open apex and associated immature supernumerary tooth with respect to tooth #21. Access preparation and minimal instrumentation was done to remove necrotic debris under copious irrigation with 2.5% sodium hypochlorite. Triple antibiotic paste was packed in the canal for four weeks. During second visit, 5 mL of whole blood was drawn from the medial cubital vein of the patient and blood was then subjected to centrifugation at 2400 rpm for 12 minutes for the preparation of Platelet rich fibrin (PRF) utilizing Choukroun's method. Triple antibiotic paste was removed and canal was dried. PRF clot was pushed to the apical region of tooth #21 using hand pluggers. Three milimetres of Mineral trioxide (MTA) was placed in cervical part of the root canal and permanent restoration was done three days later. Clinical examination at 6 and 12 months revealed no sensitivity to percussion and palpation in tooth #21and it responded positively to both electric pulp and cold tests. Radiographic examination showed resolution of periapical rarefaction, further root development and apical closure of the tooth #21 and its associated supernumerary tooth. On the basis of successful outcome of the present case it can be stated that PRF clot may serve as a scaffold for regeneration of necrotic immature teeth.